Zif-derived carbon-doped solid-state electrolyte membranes, methods of making and applications thereof

CN122907716APending Publication Date: 2026-10-13WUHAN NARI LIABILITY OF STATE GRID ELECTRIC POWER RES INST +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611392630.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但无机填料易在基体中团聚,破坏电解质膜整体结构完整性,循环过程中界面缺陷持续扩大;普通碳材料无功能性孔道与活性位点,无法抑制充放电过程中的界面副反应与锂枝晶滋生;单纯聚合物改性仅能小幅改善基体韧性,难以从根源上缓解界面失效问题

Benefits of technology

[0015]本发明选择ZIF前驱体定向碳化制备多级孔杂原子掺杂衍生碳作为功能填料,并搭配PEI-PEGDGE共聚物形成致密稳定的三维网络结构构建复合固态电解质体系,将 ZIF衍生碳均匀分散于交联网络内部,依靠PEI-PEGDGE共聚物稳定的交联骨架提升固态电解质结构耐久性,可显著提升固态电解质膜整体结构抗形变能力,延缓长循环下的结构失效;ZIF 衍生碳具备多级孔结构与杂原子活性位点,均匀分散于基体中,利用 ZIF 衍生碳的结构特性与活性位点稳定电极-电解质界面、抑制循环过程中的不良副反应与锂枝晶生长,有效缓解长循环下的性能衰减;二者协同作用,从结构强度与界面调控两方面共同强化电解质体系,大幅改善固态电池长期循环稳定性,最终制备出循环稳定性优异的固态电池,有效延长锂离子固态电池的使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907716A_ABST
    Figure CN122907716A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of solid electrolytes, in particular to a ZIF-derived carbon-doped solid electrolyte film and a preparation method and application thereof. The preparation method comprises the following steps: S1, ZIF material is calcined and carbonized to obtain ZIF-derived carbon powder ZIF-C; S2, polyethyleneimine (PEI) and polyethylene glycol diglycidyl ether (PEGDGE) are respectively dissolved in solvents to form monomer solutions; nitrogen is introduced for protection, the two monomer solutions are mixed and stirred, lithium salt and ZIF-C are added to form a mixed system; S3, the mixed system is oil-bath refluxed and stirred to prepare a film-forming solution; S4, the film-forming solution is transferred into a mold for vacuum drying, naturally cooled to room temperature, the film body is peeled off from the mold, and a composite solid electrolyte film is obtained; the ZIF material is one or more of ZIF-67, ZIF-8 and ZIF-7. The composite solid electrolyte film improves the long-term cycle stability of a solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology, and in particular to a ZIF-derived carbon-doped solid electrolyte membrane, its preparation method, and its application. Background Technology

[0002] Currently, the mainstream electrolytes for solid-state lithium batteries are divided into two major systems: inorganic solid-state electrolytes and polymer solid-state electrolytes. Both have shortcomings in cycle stability. Inorganic electrolytes are brittle and prone to cracking and interface debonding during repeated charge and discharge cycles, resulting in rapid performance degradation of the cell during cycling. Traditional polymer solid-state electrolytes have good flexibility, but insufficient bulk mechanical strength. Under long-term cycling, polymer segments are prone to irreversible deformation, and the contact interface between the electrode and electrolyte gradually deteriorates, becoming a key factor restricting the cycle life of solid-state batteries and failing to meet the requirements of long-cycle operation.

[0003] To improve the cycling stability of polymer solid electrolytes, the industry often employs optimization methods such as doping with inorganic ceramic particles, conventional carbon materials, and polymer molecular modification. However, inorganic fillers are prone to agglomeration in the matrix, disrupting the overall structural integrity of the electrolyte membrane and causing interfacial defects to continuously expand during cycling. Ordinary carbon materials lack functional channels and active sites, failing to suppress interfacial side reactions and lithium dendrite growth during charge and discharge. Simple polymer modification can only slightly improve the matrix toughness and cannot fundamentally alleviate the interfacial failure problem. Summary of the Invention

[0004] The purpose of this invention is to address the aforementioned shortcomings of the prior art by proposing a ZIF-derived carbon-doped solid electrolyte membrane, its preparation method, and its applications.

[0005] The first objective of this invention is to provide a method for preparing a ZIF-derived carbon-doped solid electrolyte membrane, comprising the following steps: S1. ZIF material is calcined and carbonized to obtain ZIF-derived carbon powder ZIF-C; S2. Polyethyleneimine (PEI) and polyethylene glycol diglycidyl ether (PEGDGE) are dissolved in solvents to form monomer solutions. Nitrogen gas is introduced throughout the process for protection. The two monomer solutions are mixed and stirred, and then lithium salt and ZIF-C are added sequentially to form a mixed system. S3. The mixture is refluxed in an oil bath and stirred to prepare a film-forming solution. S4. Transfer the film-forming liquid into a mold and vacuum dry it. Allow it to cool naturally to room temperature. Peel the membrane off the mold to obtain a composite solid electrolyte membrane. The ZIF material is one or more of ZIF-67, ZIF-8, and ZIF-7.

[0006] Furthermore, the mass ratio of ZIF-C to PEI is 0.2~0.8:1.

[0007] Furthermore, the mass ratio of PEI to PEGDGE is 1:3~5.

[0008] Furthermore, the mass ratio of lithium salt to PEI is 0.3~0.8:1.

[0009] Furthermore, the molecular weight of PEI is 800-8000; the epoxy value of PEGDGE is 0.3~0.7 mol / 100 g; and the mass concentration of the monomer in the monomer solution is 8~12%.

[0010] Furthermore, in step S3, the temperature is set to 125~140 ℃, reflux is applied, and the reaction is stirred for 3~5 h.

[0011] Furthermore, the thickness of the composite solid electrolyte membrane is 50~200 μm.

[0012] Further, in step S1, the metal salt and organic ligand are mixed in a solvent, stirred and reacted, centrifuged, washed and dried to obtain ZIF material; then, the ZIF material is calcined for 20-90 min at a heating rate of 3-8 °C / min under an inert protective atmosphere to obtain ZIF-C.

[0013] A second objective of this invention is to provide a ZIF-derived carbon-doped solid electrolyte membrane prepared by the preparation method described above.

[0014] A third objective of the present invention is to provide a lithium-ion solid-state battery comprising the aforementioned ZIF-derived carbon-doped solid electrolyte membrane.

[0015] This invention selects ZIF precursor for directional carbonization to prepare hierarchical porous heteroatom-doped derived carbon as a functional filler, and combines it with PEI-PEGDGE copolymer to form a dense and stable three-dimensional network structure to construct a composite solid electrolyte system. The ZIF-derived carbon is uniformly dispersed inside the cross-linked network. Relying on the stable cross-linked framework of PEI-PEGDGE copolymer, the structural durability of the solid electrolyte is improved, which can significantly enhance the overall structural resistance to deformation of the solid electrolyte membrane and delay structural failure under long-term cycling. The ZIF-derived carbon has a hierarchical porous structure and heteroatom active sites, which are uniformly dispersed in the matrix. The structural characteristics and active sites of ZIF-derived carbon are used to stabilize the electrode-electrolyte interface, suppress adverse side reactions and lithium dendrite growth during cycling, and effectively alleviate performance degradation under long-term cycling. The two work synergistically to strengthen the electrolyte system from both structural strength and interface regulation aspects, greatly improve the long-term cycle stability of solid-state batteries, and finally prepare solid-state batteries with excellent cycle stability, effectively extending the service life of lithium-ion solid-state batteries.

[0016] This invention also addresses the problems of low room temperature ionic conductivity, low lithium-ion transference number, poor mechanical strength, and insufficient cycle stability of existing polymer solid electrolytes by uniformly dispersing ZIF-derived carbon (especially ZIF-67-C and ZIF-8-C) with hierarchical porous structure, heteroatom doping, and high catalytic activity in the crosslinking network of PEI-PEGDGE copolymer (PEI / PEGDGE).

[0017] This invention achieves deep integration of functional fillers and polymer matrix through an integrated liquid-phase crosslinking film-forming process, avoiding the problems of easy agglomeration and poor interfacial bonding of traditional fillers. The entire preparation process is mild and the steps are closely linked, making it compatible with existing battery material mass production processes and possessing good potential for industrial application. Attached Figure Description

[0018] Figure 1 SEM image of ZIF-67 prepared in Example 1; Figure 2 SEM image of ZIF-67-C prepared in Example 1; Figure 3 XRD patterns of ZIF-67 and ZIF-67-C prepared in Example 1; Figure 4 Photographs and SEM images of the composite solid electrolyte membrane PPM-C prepared in Example 1; Figure 5 Infrared spectrum of PPM-C prepared in Example 1; Figure 6 Cycle performance graphs of solid-state pouch cells assembled for Comparative Example 1 and Example 1. Detailed Implementation

[0019] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings. However, the present invention is not limited to these embodiments.

[0020] 1. Synthesis of ZIF precursors The ZIF precursor is selected from any one of ZIF-67, ZIF-8, and ZIF-7; the metal salt is selected from at least one of soluble cobalt salts and zinc salts, specifically including cobalt nitrate hexahydrate, cobalt chloride, cobalt acetate, zinc nitrate hexahydrate, zinc chloride, and zinc acetate; the organic ligand is selected from any one of 2-methylimidazole and benzimidazole; and the reaction solvent is selected from any one of anhydrous methanol, anhydrous ethanol, and anhydrous isopropanol.

[0021] The specific steps are as follows: Prepare materials according to a molar ratio of metal salt to organic ligand of 1:5~9; prepare solutions with the following concentrations: metal salt solution molar concentration controlled at 0.06~0.12 mol / L, and organic ligand solution molar concentration controlled at 0.4~1.0 mol / L.

[0022] At room temperature, turn on the magnetic stirrer and set the stirring speed to 600~1200 rpm. Quickly pour the prepared metal salt solution into the organic ligand solution and continue stirring for 3~5 h. A solid precipitate will be generated in the system.

[0023] After the reaction is complete, centrifuge at 5000-7000 rpm for 4-8 minutes. After separation, wash the solid product 3-4 times with the corresponding anhydrous lower alcohol to remove residual unreacted raw materials.

[0024] The washed solid was placed in a vacuum drying oven, the temperature was set to 60~70 ℃, and vacuum dried for 12~20 h. After cooling, the dried ZIF precursor powder was obtained.

[0025] 2. Preparation of ZIF-derived carbon (ZIF-C) Take the dried ZIF precursor powder and spread it evenly in a ceramic crucible. Transfer the crucible into a tube furnace and continuously introduce a protective atmosphere to purge the air from the furnace.

[0026] Set the heating program for the tube furnace: heating rate 3~8 ℃ / min, from room temperature to carbonization temperature 700~900 ℃ (optimal carbonization temperature 800 ℃), and then calcining at a constant temperature for 20~90 min after reaching the target temperature.

[0027] After calcination, the product was naturally cooled in the furnace under an inert protective atmosphere until the furnace temperature was ≤40 ℃. The black solid product was then removed, and after thorough grinding and sieving, fine ZIF-derived carbon powder was obtained.

[0028] 3. Preparation of solid electrolyte membranes Polyamine monomer: Polyethyleneimine (PEI), with selectable molecular weights of 800, 2000, 5000, and 8000; Epoxy monomer: polyethylene glycol diglycidyl ether (PEGDGE), epoxy value can be selected from 0.3~0.7 mol / 100 g; Solvent: Any one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), or tetrahydrofuran (THF) may be used; Lithium salt: any one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), or lithium perchlorate (LiClO4) is selected.

[0029] The specific steps are as follows: Weigh out the two monomers according to the mass ratio of PEI:PEGDGE = 1:3~5; add PEI and PEGDGE to the selected solvent above, stir to dissolve, and prepare a homogeneous solution with a mass concentration of 8~12%.

[0030] Nitrogen gas was introduced throughout the process for protection. The two monomer solutions were mixed and stirred, and then lithium salt and ZIF-derived carbon powder were added sequentially. The mass ratio of lithium salt to PEI was 0.3~0.8:1, and the mass ratio of ZIF-C to PEI was 0.2~0.8:1.

[0031] The mixture was placed in an oil bath and the temperature was set to 125-140 °C. The reflux condenser was turned on and the mixture was stirred for 3-5 h to obtain a uniform black film-forming liquid.

[0032] Transfer the film-forming solution to any one of the following: a polytetrafluoroethylene mold, a glass mold, or a polypropylene mold; place it in a vacuum drying oven, set the temperature to 60-70 ℃, and vacuum dry for 12-20 h to completely remove the solvent.

[0033] After drying, the membrane is allowed to cool naturally to room temperature. Then, it is peeled off from the mold to obtain the composite solid electrolyte membrane. The membrane thickness can be controlled by adjusting the amount of film-forming solution and the mold area, and the finished membrane thickness is stable at 50~200 μm.

[0034] 4. Preparation and Assembly of Lithium-ion Solid-State Pouch Cells (I) Preparation of positive electrode sheet Raw material selection (multiple raw materials are available; choose one). Positive electrode active material: any one of lithium iron phosphate (LiFePO4), ternary lithium NCM523, or ternary lithium NCM622; Adhesive: Any one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), or styrene-butadiene rubber (SBR) may be selected; Conductive agent: Any one of Super-P conductive carbon black, carbon nanotubes, or graphene; The current collector is made of aluminum foil; the slurry solvent is any one of N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP).

[0035] Preparation steps: Accurately weigh the raw materials according to the mass ratio of positive electrode active material: binder: conductive agent = 8:1:1, and add an appropriate amount of selected solvent. Stir magnetically at room temperature for 4-6 hours, supplemented by ultrasonic dispersion or planetary stirring, until a uniform, particle-free, and agglomerated viscous electrode slurry is obtained.

[0036] The aluminum foil current collector was ultrasonically cleaned and dried sequentially with anhydrous ethanol and deionized water, then flattened and fixed on a coating platform. A 200-400 μm coater was used to uniformly coat the slurry onto the aluminum foil surface at a constant speed. The coated electrode was placed in a vacuum drying oven and vacuum dried at 70°C for 20-24 hours to completely remove the solvent. After drying, it was allowed to cool naturally, then cut and pressed to the designed dimensions to obtain a regular positive electrode sheet, which was then stored in a dry, sealed environment for later use.

[0037] (II) Preparation of liquid electrolyte The electrolyte solute can be any one of lithium hexafluorophosphate (LiPF6) or lithium tetrafluoroborate (LiBF4), with a uniform solute molar concentration of 1 mol / L; the electrolyte solvent can be any one of the following systems: System 1: Ethylene carbonate (EC): Dimethyl carbonate (DMC): Diethyl carbonate (DEC) = 1:1:1 (volume ratio); System 2: Ethylene carbonate (EC): Ethyl methyl carbonate (EMC) = 1:1 (volume ratio).

[0038] All operations were performed in an argon atmosphere glove box with water and oxygen content both <0.01ppm, and the mixture was sealed and stored away from light after preparation.

[0039] (III) Solid-state pouch cell assembly 1. Transfer all assembly components, including aluminum-plastic film, lithium metal anode, composite solid electrolyte membrane of this invention, positive electrode sheet, and tabs, to an argon glove box. Assembly can only proceed after the water and oxygen content is stable at <0.01ppm.

[0040] 2. Employing a classic stacking process, lithium metal anode, composite solid electrolyte membrane, and positive electrode are stacked sequentially, ensuring complete alignment, no misalignment, and no wrinkles among the layers. A small amount of electrolyte (1-2 drops) is added to each layer interface solely for wetting and to eliminate contact resistance. Multiple layers of electrodes and electrolyte membranes can be repeatedly stacked according to capacity requirements to assemble a complete bare cell.

[0041] 3. An ultrasonic spot welding machine is used inside the glove box to weld the positive and negative electrode tabs to the positive and negative current collector ends of the battery cell, respectively. The welding is firm and there are no incomplete welds or desoldering.

[0042] 4. Place the molded aluminum-plastic film flat, put the bare battery cells into the groove of the aluminum-plastic film, and arrange them neatly; use a soft-pack battery sealing machine to heat seal the sides and bottom first, and leave the liquid injection / venting port.

[0043] 5. After the encapsulated cell is left to stand at room temperature for 4-6 hours, the electrolyte will fully wet the electrode and electrolyte interface. After standing, vacuum the air and exhaust the air. Finally, complete the full sealing to obtain a complete solid-state soft-pack battery.

[0044] 6. Once assembled, the soft-pack battery is allowed to stand at room temperature for activation before undergoing various electrochemical performance tests, such as rate capability, cycle life, and impedance.

[0045] Example 1 In this embodiment, ZIF-67 is used as a precursor to prepare ZIF-derived carbon, and then a composite solid electrolyte membrane is prepared.

[0046] 1. Synthesis of ZIF-67 precursor Cobalt nitrate hexahydrate was selected as the metal salt, 2-methylimidazole as the organic ligand, and anhydrous methanol as the reaction solvent. A 0.09 mol / L cobalt nitrate hexahydrate methanol solution and a 0.7 mol / L 2-methylimidazole methanol solution were prepared. The mixture was magnetically stirred at 900 rpm at room temperature, and the metal salt solution was rapidly poured into the ligand solution, maintaining a metal salt to organic ligand molar ratio of 1:7. The reaction was continued with stirring for 4 h. After the reaction was complete, the mixture was centrifuged at 6000 rpm for 6 min, and the solid product was washed three times with anhydrous methanol and dried in a vacuum drying oven at 65 ℃ for 16 h to obtain ZIF-67 powder.

[0047] 2. Preparation of ZIF-67 derived carbon ZIF-67 powder was spread evenly on a ceramic crucible, transferred into a tube furnace and protected with argon gas; the temperature was increased to 800 ℃ at 5 ℃ / min, calcined at a constant temperature for 55 min, cooled to below 40 ℃ in an inert atmosphere, and then ground and sieved to obtain ZIF-67-C powder.

[0048] 3. Preparation of PPM-C composite solid electrolyte membrane Polyethyleneimine (PEI) with a molecular weight of 2000, polyethylene glycol diglycidyl ether (PEGDGE) with an epoxy value of 0.5 mol / 100 g, DMF were selected as solvents, and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was selected as lithium salt.

[0049] Two monomer solutions with a mass concentration of 10% were prepared and mixed under nitrogen protection, with a PEI:PEGDGE mass ratio of 1:4. Lithium salt and ZIF-67-C were added sequentially, with a lithium salt to PEI mass ratio of 0.5:1 and a ZIF-67-C to PEI mass ratio of 0.5:1. The mixture was placed in a 130 °C oil bath and refluxed with stirring for 4 h to obtain a black film-forming solution. The film-forming solution was injected into a polytetrafluoroethylene mold and vacuum dried at 65 °C for 16 h to remove the solvent. Demolding yielded a 120 μm thick composite solid electrolyte membrane, PPM-C.

[0050] 4. Battery Assembly Lithium iron phosphate was used as the positive electrode active material, and the positive electrode sheet was prepared according to the ratio of positive electrode active material: binder: conductive agent = 8:1:1. A lithium metal-based solid-state soft-pack battery was assembled according to the stacking process using 1 mol / L LiPF6 electrolyte (EC:DMC:DEC = 1:1:1). A small amount of electrolyte was added to the interface for wetting, and after encapsulation and static activation, the cycle stability test was carried out.

[0051] Example 2 In this embodiment, ZIF-8 is used as a precursor to prepare ZIF-derived carbon, and the remaining basic processes are consistent with those in Example 1.

[0052] 1. Synthesis of ZIF-8 precursor Zinc nitrate hexahydrate was selected as the metal salt, 2-methylimidazole as the organic ligand, and anhydrous ethanol as the reaction solvent. A 0.09 mol / L zinc nitrate hexahydrate ethanol solution and a 0.7 mol / L 2-methylimidazole ethanol solution were prepared with a metal salt to organic ligand molar ratio of 1:7. The mixture was stirred at 900 rpm at room temperature and reacted for 4 h. After centrifugation at 6000 rpm for 6 min, the mixture was washed three times with anhydrous ethanol and dried under vacuum at 65 ℃ for 16 h to obtain ZIF-8 powder.

[0053] 2. Preparation of ZIF-8 derived carbon Argon gas was introduced into a tube furnace, and the temperature was increased to 800 ℃ at 5 ℃ / min. The furnace was then calcined at a constant temperature for 55 min, cooled under an inert atmosphere, ground, and sieved to obtain ZIF-8-C powder.

[0054] 3. Preparation of composite solid electrolyte membranes The monomers, solvents, lithium salt types and ratios, reaction conditions, drying processes, and film thickness control were all the same as in Example 1, except that the filler was replaced with ZIF-8-C, and a composite solid electrolyte membrane was finally obtained.

[0055] 4. Battery assembly and testing The cathode formulation, electrolyte system, battery assembly process, and testing conditions are completely consistent with those in Example 1.

[0056] Example 3 In this embodiment, ZIF-67 is used as the precursor. The raw material ratio and carbonization parameters are adjusted, while the rest of the process remains unchanged.

[0057] 1. Synthesis of ZIF-67: The molar ratio of metal salt to organic ligand was adjusted to 1:5, the concentration of metal salt solution was 0.06 mol / L, the concentration of organic ligand solution was 0.4 mol / L, the stirring speed was 600 rpm, and the reaction was carried out for 3 h; centrifugation at 5000 rpm for 4 min, washing 4 times with anhydrous methanol, and vacuum drying at 60 ℃ for 12 h were obtained to obtain the ZIF-67 precursor.

[0058] 2. Carbonization process: The tube furnace is heated at a rate of 3 ℃ / min, heated to 700 ℃, calcined at a constant temperature for 20 min, and then cooled to obtain ZIF-67-C.

[0059] 3. Electrolyte preparation: PEI with a molecular weight of 800 and PEGDGE epoxy value of 0.3 mol / 100 g was selected, with a PEI:PEGDGE mass ratio of 1:3; LiFSI was selected as the lithium salt, with a lithium salt to PEI mass ratio of 0.3:1 and a ZIF-67-C to PEI mass ratio of 0.2:1; THF was used as the solvent, the solution concentration was prepared at 8%, the reaction was carried out in an oil bath at 125 ℃ for 3 h, and then vacuum dried at 60 ℃ for 12 h to obtain an electrolyte membrane with a thickness of 50 μm.

[0060] 4. Battery assembly and testing: Same as in Example 1.

[0061] Example 4 In this embodiment, ZIF-67 was used as a precursor, and the filler addition amount, reaction temperature and solvent system were further optimized.

[0062] 1. The ZIF-67 precursor and carbonization process were kept the same as in Example 1 to obtain ZIF-67-C.

[0063] 2. Electrolyte preparation: PEI with a molecular weight of 5000 and PEGDGE with an epoxy value of 0.7 mol / 100 g were selected. In the mixed system, the mass ratio of PEI to PEGDGE was 1:5. DMAc was selected as the solvent, and the mass concentration of each monomer was 12%. LiClO4 was selected as the lithium salt, with a mass ratio of lithium salt to PEI of 0.8:1 and a mass ratio of ZIF-67-C to PEI of 0.8:1. The reaction was carried out in an oil bath at 140 ℃ for 5 h under nitrogen protection, followed by vacuum drying at 70 ℃ for 20 h to obtain an electrolyte membrane with a thickness of 200 μm.

[0064] 3. Battery assembly and testing: Same as in Example 1.

[0065] Example 5 This embodiment uses ZIF-67 as a precursor, adjusts the limiting process parameters throughout the entire process, and explores the impact of the process window on cycle stability.

[0066] 1. Synthesis of ZIF-67: The molar ratio of metal salt to organic ligand was 1:9, the concentration of metal salt solution was 0.12 mol / L, the concentration of organic ligand solution was 1.0 mol / L, the stirring speed was 1200 rpm, and the reaction was carried out for 5 h. After centrifugation at 7000 rpm for 8 min, the mixture was washed 3 times with anhydrous methanol and dried under vacuum at 70 ℃ for 20 h to obtain ZIF-67.

[0067] 2. Carbonization process: Heating rate 8 ℃ / min, heating to 900 ℃, constant temperature calcination for 90 min to obtain ZIF-67-C.

[0068] 3. Electrolyte preparation: The monomer ratio, lithium salt, and solvent were the same as in Example 1. The mass ratio of ZIF-67-C to PEI was 0.6:1. The reaction was carried out in an oil bath at 135 °C for 4.5 h and then vacuum dried at 68 °C for 18 h to prepare the composite electrolyte membrane.

[0069] 4. Battery assembly and testing: Same as in Example 1.

[0070] Comparative Example 1 (without ZIF-derived carbon) The raw materials, proportions, reaction process, film formation conditions, and battery assembly process were completely consistent with those in Example 1. The difference was that no ZIF-derived carbon filler was added, and the solid electrolyte membrane PPL was prepared by cross-linking PEI and PEGDGE. Subsequently, solid soft-pack batteries of the same system were assembled and cycle stability comparison tests were conducted.

[0071] Comparative Example 2 (adding ordinary conductive carbon powder to replace ZIF-derived carbon) The overall process, raw material ratio, and preparation process are the same as in Example 1. ZIF-67-C is replaced with an equal amount of conventional Super-P conductive carbon black, while the other parameters, battery assembly, and testing conditions remain unchanged. Ordinary carbon powder modified solid electrolyte membranes are prepared for performance comparison.

[0072] Comparative Example 3 (Inorganic Ceramic Filler Modification System) The overall process, monomer and lithium salt ratio are the same as in Example 1. ZIF-67-C is replaced with an equal amount of nano-silica inorganic ceramic filler. The filler addition amount, reaction conditions, film formation process and battery assembly method are the same as in Example 1. Inorganic ceramic doped solid electrolyte membrane is prepared and cycle stability comparison test is carried out.

[0073] Figure 1 The ZIF-67 SEM image prepared in Example 1 clearly shows that the product exhibits a typical dodecahedral morphology, with sharp edges and regular shapes. The individual crystals are uniform in size, and the overall particle size distribution range is narrow. No obviously irregular or broken particles are observed. Furthermore, the particles exhibit excellent dispersibility, existing independently without large-area adhesion or agglomeration. The surfaces are smooth, and the crystal outlines are complete.

[0074] The results show that the synthesis process parameters such as the ratio, reaction temperature, and stirring rate used in this invention are reasonable and controllable, and can efficiently prepare ZIF-67 precursors with high crystallinity, regular morphology, and excellent monodispersity. The regular crystal framework also provides a reliable precursor structure guarantee for the subsequent high-temperature carbonization construction of hierarchical porous carbon materials.

[0075] Figure 2 The SEM image of ZIF-67-C prepared in Example 1 shows that, compared with the morphology of the original ZIF-67 precursor, the carbonized material retains the macroscopic framework morphology of the precursor intactly, without problems such as framework collapse, pulverization, or fragmentation, exhibiting good structural integrity. Under high-temperature pyrolysis, the crystal surface transforms from its original smooth state to a rough, porous state, with numerous micropores and mesopores interconnected to form a multi-level pore structure. The pores are evenly distributed and highly porous.

[0076] This hierarchical porous structure not only increases the specific surface area of ​​the material and provides a large number of active sites, but also constructs continuous ion transport channels after being incorporated into the polymer matrix. At the same time, the porous carbon skeleton can further enhance the overall structural toughness of the electrolyte, which is an important structural basis for improving the cycle stability of the system.

[0077] Figure 3 The XRD patterns of ZIF-67 and ZIF-67-C from Example 1 are shown in the figures. These XRD patterns correspond to the pure ZIF-67 precursor and the ZIF-67-C sample after high-temperature carbonization, respectively. As can be seen from the figures, the ZIF-67 curve exhibits a series of high-intensity, sharp-shaped, and stable characteristic diffraction peaks at the characteristic diffraction angles, perfectly matching the peak positions of the standard ZIF-67 crystal card. This further verifies that the synthesized product has high phase purity, a well-developed crystal structure, and no obvious impurity phase formation. After calcination in an inert atmosphere at 700–900 °C, all the characteristic crystal diffraction peaks of ZIF-67 completely disappear, and the pattern shows typical broadened diffuse diffraction bumps in the 20°–30° range, which is a typical diffraction characteristic of amorphous carbon materials.

[0078] This phenomenon proves that the high-temperature carbonization process completely destroys the organometallic framework crystal structure of ZIF-67, the organic ligands are completely pyrolyzed, the precursor is successfully transformed into an amorphous carbon matrix, and the metal active components are uniformly embedded in the carbon skeleton, realizing an effective transformation from a crystalline precursor to a functional carbon material.

[0079] Figure 4Figure 4 shows a photograph and SEM image of the composite solid electrolyte membrane PPM-C prepared in Example 1. Figure 4(a) shows the photograph of the composite solid electrolyte membrane; the membrane surface is smooth and uniform in thickness, with no pinholes, cracks, bubbles, or other defects. The membrane exhibits good flexibility and bending performance, and can be bent freely without breaking, indicating that the composite membrane has excellent machinability and can meet the assembly process requirements for battery stacking and packaging. Figure 4(b) shows a cross-sectional SEM image of the composite solid electrolyte membrane. ZIF-67-C particles are uniformly embedded in the PEI-PEGDGE copolymer matrix, with no local enrichment, agglomeration, or phase separation. The filler and polymer matrix interface are tightly bonded with very few interfacial gaps. This continuous and dense composite network structure can resist stress deformation during repeated charge-discharge cycles, preventing interfacial delamination and ensuring the long-term stability of the electrolyte system at the microstructural level.

[0080] Figure 5 The infrared spectrum of PPM-C prepared in Example 1 was analyzed using standard infrared data from existing literature, focusing on the characteristic absorption peaks at 910 cm⁻¹. -1 The characteristic absorption peaks originally attributed to the epoxy three-membered ring of polyethylene glycol diglycidyl ether (PEGDGE) have largely disappeared, while the absorption peaks of polyethyleneimine (PEI) in the 3280–3450 cm⁻¹ range have also disappeared. -1 The NH stretching vibration peak, 1602 cm⁻¹ -1 The intensity of the amino bending vibration peak was significantly reduced and the peak position shifted slightly, proving that the amino group of PEI and the epoxy group of PEGDGE underwent a ring-opening crosslinking reaction, and the PEI-PEGDGE copolymer network structure was successfully constructed. 2858~2953 cm in the atlas -1 A peak for the stretching vibration of saturated CH on the alkyl chain appears at 1188 cm⁻¹. -1 The presence of strong and broad aliphatic COC ether bond characteristic peaks further confirms the integrity and stability of the PEI-PEGDGE copolymer skeleton structure.

[0081] The spectrum also detected characteristic signals of ZIF-derived nitrogen-doped carbon at 1378 cm⁻¹. -1 The peak represents the CN stretching vibration of the carbon skeleton. The full spectrum shows a stable baseline with no additional impurities, comprehensively confirming the good chemical compatibility of the ZIF-derived carbon, lithium salt, and PEI-PEGDGE copolymer matrix. The composite electrolyte membrane exhibits a stable chemical structure and can maintain its composition and structure unchanged during battery operation and long-term cycling.

[0082] Electrochemical performance testing Cyclic stability test: Each group of solid-state pouch batteries was placed in a constant-temperature test environment (room temperature, 25℃±2℃) and constant-current charge-discharge cycle tests were conducted using the Blue Battery Testing System. The test voltage range was set to 2.5 V~4.2 V, and the charge-discharge rate was uniformly 0.2 C. During the charging phase, a constant-current charging mode was used. After reaching the cutoff voltage, the battery was allowed to rest for 5 minutes, followed by constant-current discharge until the discharge cutoff voltage. After each charge-discharge cycle, the battery was allowed to rest for another 5 minutes, and this cycle was repeated for a total of 70 cycles. The discharge specific capacity, coulombic efficiency, and other data were recorded for each cycle. Finally, the discharge specific capacity of each group of batteries after 70 cycles was calculated to evaluate the long-term cycle stability of different electrolyte systems. All batteries under test maintained the same assembly process, electrode system, amount of interfacial wetting electrolyte, and packaging conditions to eliminate the interference of irrelevant variables on the test results. The discharge specific capacity of each group of samples after 70 cycles is detailed in Table 1 below. Figure 6 .

[0083] Ion conductivity test: The obtained solid electrolyte membrane was sandwiched between two stainless steel blocking electrodes to assemble an SS|SPE|SS test cell. AC impedance spectroscopy was performed at 25 °C using an electrochemical workstation, with a test frequency range of 1×10⁻⁶. -2 Hz~1×10 6 Hz. The resistance R is obtained from the high-frequency intercept of the impedance spectrum, and then calculated according to the formula: Calculate the room temperature ionic conductivity, where L is the film thickness and A is the electrode contact area.

[0084] Lithium-ion transference number test: A solid electrolyte membrane was assembled into a Li|SPE|Li symmetric cell. Polarization was performed by applying a 10mV overpotential at 25 °C. After the current stabilized, AC impedance testing was conducted again. Based on the impedance before and after polarization and the steady-state current, the lithium-ion transference number was calculated using the Bruce-Vincent method.

[0085] in: Lithium-ion transference number; : Overpotential (V) applied during polarization; Initial polarization current (A); : The current after reaching steady state (A); : Interface resistance (Ω) measured by AC impedance before polarization; : Interface resistance (Ω) measured by AC impedance after polarization stabilization.

[0086] The test results of ionic conductivity and lithium-ion transference number for each group of samples are detailed in Table 1 below.

[0087] Table 1

[0088] As can be seen from the table above, under the same test conditions, Comparative Example 1 exhibits prominent interface degradation and side reaction problems, resulting in significant capacity decay. After 70 cycles, its discharge specific capacity is only 112 mAh / g. Comparative Example 2 uses Super-P conductive carbon black to modify the electrolyte. However, carbon black lacks a hierarchical porous structure and heteroatom active sites, thus offering limited improvement in interface stability. After 70 cycles, its discharge specific capacity is 116 mAh / g. Comparative Example 3 is doped with nano-silica inorganic ceramic filler. The filler is prone to agglomeration in the matrix and generates interface defects, leading to a faster battery cycle decay rate. After 70 cycles, its discharge specific capacity is 114 mAh / g. In contrast, the modified samples of the various embodiments of this invention exhibit significant advantages: Example 1, using ZIF-67-C as the functional filler, demonstrates excellent interfacial stability, maintaining a stable discharge specific capacity of 134 mAh / g after 70 cycles; Example 2, using ZIF-8-C as the functional filler, also exhibits good cycle retention, with a discharge specific capacity of 131 mAh / g after 70 cycles; Example 3, by adjusting the precursor synthesis, carbonization, and electrolyte ratio parameters, achieves a discharge specific capacity of 127 mAh / g after 70 cycles; Example 4, by increasing the filler doping amount and optimizing the reaction conditions, achieves a discharge specific capacity of 132 mAh / g after 70 cycles; Example 5, using extreme process parameters, achieves a discharge specific capacity of 129 mAh / g after 70 cycles. All the batteries in these embodiments maintain stable coulombic efficiency with minimal fluctuations during long-term cycling, demonstrating a capacity retention rate far superior to the three comparative examples.

[0089] Figure 6 In Figure 'a', the cycle performance diagram of the solid-state pouch cell assembled in Example 1 is shown. Figure 6Figure b shows the cycle performance of the solid-state pouch battery assembled in Comparative Example 1. The test results clearly show that the solid-state pouch battery prepared in Comparative Example 1 exhibits a continuous and rapid decline in discharge capacity with increasing cycle count, significant fluctuations in coulombic efficiency, and persistently intensified interface degradation and side reactions during long cycles, resulting in a short cycle life. After 70 cycles, the discharge specific capacity is only 112 mAh / g. In contrast, the solid-state pouch battery prepared in Example 1, under the same test conditions and cycle period, maintains a consistently high discharge capacity retention rate, stable coulombic efficiency with minimal fluctuations, and a discharge specific capacity of 134 mAh / g after 70 cycles. This comparative result directly demonstrates that the composite solid electrolyte membrane prepared in this invention can effectively suppress interfacial side reactions during charging and discharging, alleviate structural deformation and lithium dendrite growth, greatly improve the interfacial stability between the electrode and electrolyte, and significantly enhance the long-cycle service capability of solid-state batteries.

[0090] The above results fully demonstrate that ZIF-derived carbon, with its hierarchical porous structure and heteroatom active sites, can effectively suppress structural deformation, interfacial side reactions and lithium dendrite growth during charging and discharging. It also forms a synergistic effect with the PEI-PEGDGE copolymer crosslinking network, significantly improving the stability of the electrode-electrolyte interface and the long-cycle service performance of the battery.

[0091] For any points not covered above, existing technologies shall apply.

[0092] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a ZIF-derived carbon-doped solid electrolyte membrane, characterized in that, Includes the following steps: S1. ZIF material is calcined and carbonized to obtain ZIF-derived carbon powder ZIF-C; S2. Polyethyleneimine (PEI) and polyethylene glycol diglycidyl ether (PEGDGE) are dissolved in solvents to form monomer solutions. Nitrogen gas is introduced throughout the process for protection. The two monomer solutions are mixed and stirred, and then lithium salt and ZIF-C are added sequentially to form a mixed system. S3. The mixture is refluxed in an oil bath and stirred to prepare a film-forming solution. S4. Transfer the film-forming liquid into a mold and vacuum dry it. Allow it to cool naturally to room temperature. Peel the membrane off the mold to obtain a composite solid electrolyte membrane. The ZIF material is one or more of ZIF-67, ZIF-8, and ZIF-7.

2. The preparation method according to claim 1, characterized in that, The mass ratio of ZIF-C to PEI is 0.2~0.8:

1.

3. The preparation method according to claim 1, characterized in that, The mass ratio of PEI to PEGDGE is 1:3~5.

4. The preparation method according to claim 1, characterized in that, The mass ratio of lithium salt to PEI is 0.3~0.8:

1.

5. The preparation method according to claim 1, characterized in that, PEI has a molecular weight of 800-8000; PEGDGE has an epoxy value of 0.3-0.7 mol / 100 g; and the monomer concentration in the monomer solution is 8-12%.

6. The preparation method according to claim 1, characterized in that, In step S3, the temperature is set to 125~140 ℃, reflux is applied, and the reaction is stirred for 3~5 h.

7. The preparation method according to claim 1, characterized in that, The thickness of the composite solid electrolyte membrane is 50~200 μm.

8. The preparation method according to claim 1, characterized in that, In step S1, the metal salt and organic ligand are mixed in a solvent, stirred and reacted, centrifuged, washed and dried to obtain ZIF material; then the ZIF material is calcined for 20-90 min at a heating rate of 3-8 °C / min under an inert protective atmosphere to obtain ZIF-C.

9. A ZIF-derived carbon-doped solid electrolyte membrane prepared by the preparation method according to any one of claims 1-8.

10. A lithium-ion solid-state battery, characterized in that, Includes the ZIF-derived carbon-doped solid electrolyte membrane as described in claim 9.